ICT in teacher education: Examining needs, expectations and attitudes - Zuochen Zhang; Dragana Martinovic (The Canadian Network for Innovation in Education (CNIE), 2009)
An exploratory case study was designed to obtain pre-service teachers' expectations of and attitudes toward the learning and integrating of Information and Communication Technologies (ICT) into their teaching and learning. Given the diverse demographic backgrounds and social conditions of the teacher candidates, such as age, gender, English language proficiency, and previous education, a wide range of responses to the online survey and the semi-structured focus group interview questions was expected. Implementation of the sequential mixed method research design resulted in emerging themes related to participants' social conditions that impact their perceptions and attitudes regarding the ICT and beliefs about the use of ICT in their future careers. Findings from this study are compared to earlier studies done in the same setting. Findings from this case study show unexpected consistency in teacher candidates' comments despite changed circumstances. This study could be employed as a useful reference for the design of an ICT curriculum for Teacher Education programs. Résumé : Une étude de cas exploratoire a été conçue afin de connaître les attentes et les dispositions des futurs enseignants à l'égard de l'apprentissage et de l'intégration des technologies de l'information et de la communication (TIC) dans leur pratique d'enseignement et leur apprentissage. L'obtention d'un large éventail de réponses à l'enquête en ligne et aux questions semi-structurées du groupe de discussion était prévue compte tenu de la diversité des horizons démographiques et des conditions sociales des candidats (notamment l'âge, le sexe, le niveau de connaissance de l'anglais et la formation antérieure). L'utilisation de la méthode de recherche séquentielle mixte a conduit à l'émergence de thèmes liés aux conditions sociales des participants, conditions qui influencent leurs perceptions et leurs dispositions à l'égard des TIC ainsi que leurs opinions au sujet de l'utilisation des TIC dans leur future carrière. Les résultats de cette étude sont comparés à des études antérieures effectuées dans un cadre similaire. Les résultats de cette étude de cas révèlent une cohérence inattendue des commentaires des futurs enseignants malgré des différences circonstancielles. Cette étude pourrait être utilisée en tant qu'outil de référence utile pour la conception de cours sur les TIC à l'intérieur des programmes de formation des enseignants.